2012
DOI: 10.1007/s11064-012-0893-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selenium and Topiramate on Cytosolic Ca2+ Influx and Oxidative Stress in Neuronal PC12 Cells

Abstract: It has been widely suggested that selenium (Se) deficiency play an important role in the pathophysiology of epilepsy. It has been reported that Se provides protection against the neuronal damage in patients and animals with epilepsy by restoring the antioxidant defense mechanism. The neuroprotective effects of topiramate (TPM) have been reported in several studies but the putative mechanism of action remains elusive. We investigated effects of Se and TPM in neuronal PC12 cell by evaluating Ca(2+) mobilization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 37 publications
2
26
1
1
Order By: Relevance
“…These studies showed that TPM has been proposed as a putative agent in the treatment of some neurodegenerative disorders . Recent studies have suggested that the mechanism of action of TPM in neuroprotection is the inhibition of Ca 2+ ion entry and Protein kinase C (PKC) . Recent findings also suggest that TPM can attenuate oxidative stress and mitochondrial dysfunction .…”
Section: Introductionmentioning
confidence: 68%
“…These studies showed that TPM has been proposed as a putative agent in the treatment of some neurodegenerative disorders . Recent studies have suggested that the mechanism of action of TPM in neuroprotection is the inhibition of Ca 2+ ion entry and Protein kinase C (PKC) . Recent findings also suggest that TPM can attenuate oxidative stress and mitochondrial dysfunction .…”
Section: Introductionmentioning
confidence: 68%
“…These proteins, to a certain degree, affect caspase activation by controlling the release of cytochrome C from the mitochondria, which in turn interacts with the adapter protein Apaf-1, resulting in the activation of pro-Caspase-9 (30). The disturbance of intracellular free Ca 2+ ions is another key event when cells are exposed to damaging stress (3133). In the present study, apoptosis was inhibited in MDR cells.…”
Section: Discussionmentioning
confidence: 99%
“…If the free radical production increases proportionally to the consumption of GSH-Px enzyme activities, GSH levels also decline. Recently, we observed a decrease in Ca 2+ entry, MMCA activity, and oxidative stress values in experimental neuronal diseases such as epilepsy and pain, although selenium administration induced protective effects on the values in human, rat, and cell lines [15][16][17]37]. The results of a few reports indicated that oxidative stress levels were high in patients with migraines and rats with CSD [6,7,11].…”
Section: Discussionmentioning
confidence: 99%
“…Selenium is incorporated in mammalian proteins as selenocysteine or selenomethionine, both of which are dietary forms of selenium, although selenomethionine is the major form [13,14]. Selenium is implicated as the neuroprotective agent in several neuronal diseases including epilepsy [15,16] and pain [17]. The neuroprotective effects of selenium are attributed to its ability to inhibit apoptosis and mitochondrial oxidative stress [18] and to modulate Ca 2+ influx through cation channels such as TRP melastatin 2 (TRPM2) channels [19,20].…”
Section: Introductionmentioning
confidence: 99%